1998
DOI: 10.1038/sj.onc.1201598
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the specific DNA binding activity of Xenopus laevis p53: evidence for conserved regulation through the carboxy-terminus of the protein

Abstract: Recombinant human p53 isolated either from E. coli or from insect cells is poorly active for binding to DNA but it can be dramatically stimulated by phosphorylation, antibody binding to the carboxy-terminal negative regulatory domain, short peptides derived from this negative regulatory domain or short single strands of DNA. We report here that Xenopus p53 has a very similar behavior. Using a new set of monoclonal antibodies directed either to the amino-or the carboxyterminus of Xenopus p53, we demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Homology in the amino-terminus is restricted to the mdm2 binding site whereas the homology in the carboxy-terminus is localized in the oligomerization domain. We have produced several panels of mAbs toward human and xenopus p53 (Legros et al, 1994a;Hardy-Bessard et al, 1998). About 60% of these mAbs recognized an immunodominant epitope localized in the amino-terminus of the p53 that contains the binding site of p53 to mdm2 ( Figure 1B).…”
Section: P53 P73 and P63 Cross Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Homology in the amino-terminus is restricted to the mdm2 binding site whereas the homology in the carboxy-terminus is localized in the oligomerization domain. We have produced several panels of mAbs toward human and xenopus p53 (Legros et al, 1994a;Hardy-Bessard et al, 1998). About 60% of these mAbs recognized an immunodominant epitope localized in the amino-terminus of the p53 that contains the binding site of p53 to mdm2 ( Figure 1B).…”
Section: P53 P73 and P63 Cross Reactivitymentioning
confidence: 99%
“…These findings are totally in accordance with the work performed in mice on the production of p53 monoclonal antibodies (mAbs). Immunization of mice with either murine, xenopus or human wild-type p53 led to the production of mAbs directed to linear epitopes localized in the amino-and carboxy-terminus of p53 (Vojtesek et al, 1992;Bartek et al, 1993;Legros et al, 1994a;Hardy-Bessard et al, 1998). MAbs specific for the central region of the protein were obtained only after a special immunization or selection procedure (Legros et al, 1994b;Vojtesek et al, 1995).…”
mentioning
confidence: 99%
“…The regulation of p53 via mdm2 protein is also conserved throughout evolution, and it has been shown that xdm2 is able to bind mammalian p53 (Kussie et al, 1996;Marechal et al, 1997). The binding of hdm2 to Xp53 led to inactivation of the transactivational activity of p53 (Hardy-Bessard et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally assumed that this consensus is conserved in the mouse, but no systematic studies have been performed to verify this point. The main argument suggesting that this consensus could be conserved in various species is derived from the finding that X. laevis p53 binds efficiently to this consensus sequence in a similar way to human p53 (Hardy-Bessard et al, 1998). X. laevis p53 also efficiently transactivates human p53 target genes, such as p21WAF1 or bax.…”
Section: The P53 Familymentioning
confidence: 99%
“…This is the first time that p53 RE has been reported in nonmammalian species. Experimental evidence is necessary to demonstrate the biological activity of these sequences, but several lines of experimental evidence already suggest that mammalian and X. laevis p53 are interchangeable and behave in similar ways (Hardy-Bessard et al, 1998;Bensaad et al, 2001).…”
Section: Other P53 Target Genesmentioning
confidence: 99%